ANALISIS KONFLIK MASYARAKAT DAN PEMERINTAH TERHADAP DAMPAK TRANSPORTASI ANGKUTAN PERTAMBANGAN BATU BARA DI KABUPATEN INDRAGIRI HULU - Fajar Alan Syahrier; Galank Pratama; Jefri Al Kausar; Mirza Sazeta (LPPM Universitas Abdurrab, 2024)
The existence of coal mines in Indragiri Hulu Regency is a sector that functions to increase Regional Original Income (PAD) if managed well, but the existence of coal mine transportation activities using public roads has triggered conflict between the Indragiri Hulu Regency Government and the local community. This conflictual relationship cannot be separated from the ecological impact caused by coal mining activities, where the local government has no commitment to maintaining the quality of the community's environment. In this research, the author wants to analyze the dynamics of conflict between civil society and the Indragiri Hulu Regency Government regarding coal mining activities in Indragiri Hulu Regency. This research uses qualitative methods. The results of the research are that there is public distrust in the Regional Government regarding policies governing the transportation of mining products which tend to benefit mining companies, in the principle negotiation aspect there are differences in views between the Regional Government and the community regarding coal transportation activities using public roads, and the needs of residents which is hampered by the impact of coal mining transportation.